A188 BIRTH COHORT SCREENING FOR HEPATITIS C IN AN OUTPATIENT ENDOSCOPY UNIT: INTERIM RESULTS. (15th March 2019) - Rai, M; Lowe, C; McKay, J; Flemming, J
Abstract: Background: Chronic hepatitis C (HCV) is a curable asymptomatic infection and it is estimated that as many as 70% of infected patients remain undiagnosed. The Canadian Liver Foundation recommends one-time HCV screening in all Canadians born from 1945–1975. Aims: The aim of this study is to determine the acceptance, feasibility and cost effectiveness of an HCV screening program in this birth cohort in an outpatient endoscopy setting. Here we present the interim results. Methods: We are conducting a 12-month prospective cohort study of individuals born from 1945–1975 presenting to the outpatient endoscopy unit at the Kingston Health Sciences Centre. Patients scheduled for an endoscopic procedure within this birth cohort who do not have results of previous HCV testing are approached for inclusion. After informed consent, HCV screening is performed using the point-of-care OraSure® test for the HCV antibody. Those with a positive screening test have blood sent to Public Health Ontario for HCV RNA and genotyping. If RNA positive, they are linked to care. Results: During the first 6 months, 55% (628/1145) of eligible patients were approached for inclusion (Table) and 83% (522/628) consented for HCV screening (50% female, median age 62 years [IQR 55–68 years], 87% Caucasian race). Of those who consented, 85% of patients had no previous HCV screening and 6% were screened but unaware of their screening status. Overall, 0.8% (4/522) of patients screened positive for the HCV antibody using the OraSure® test. All four patients have been seen in outpatient follow-up and are undergoing evaluation for HCV therapy. Conclusions: The majority of patients born from 1945–1975 presenting for outpatient endoscopy have not been screened for HCV. This identifies a target population for the development of an HCV screening program with a goal of to increasing HCV identification and facilitating linkage to care. The final results of this study will be used to perform a cost-effective analysis of the implementation of this model of HCV screening. Funding Agencies: Southeastern Ontario Academic Medical Organization (SEAMO) Innovation Fund and Gilead Canada.